Prevalence of blindness and visual impairment and its causes among people aged 50 years and above in Karnali Zone, Nepal - Dulal, S; Sapkota, Y D (Nepalese Journal of Ophthalmology, 2012)
Objective: To estimate the prevalence of blindness and visual impairment and its causes among those aged 50 years and above in Karnali Zone. Materials and methods: Stratified cluster sampling method was used. Twenty four clusters of 50 people aged 50 years and above were selected for the study. Visual acuity was recorded with simplified vision testing card with one optotype “E” of size 60 on one side and size 18 on the other side. Examination by ophthalmologist under mydriasis was done for those with a pinhole visual acuity of less than 6/18. Results: Of 1200 enumerated persons 1,174 were examined (97.8% response rate). The prevalence of blindness (VA